THE ELDERLY AS VICTIMS OF VIOLENT CRIME: A REPORT OF TWO CASES (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Elderly people are susceptible populace for violent crime or abuse and neglect. About 7%  of India's population are composed of elder persons and with improvements in  socioeconomic conditions and increasing life expectancy, it is expected that this group  may increase further. This increase of elder population has expanded a potential group of  crime victims who are vulnerable to violence. The present case report summarizes two  cases of elder homicides and addresses the issue. Some measures are also suggested to  prevent the violence and death within this vulnerable population.
Keywords: Elder; homicide; elder care